Fine Mapping of the Subunit Binding Sites of Influenza Virus RNA Polymerase - Ohtsu, Yasushi; Honda, Yoshikazu; Sakata, Yasutaka; Kato, Hirohisa; Toyoda, Tetsuya (Wiley, 2002)
Influenza virus RNA polymerase consists of three subunits, PB1, PB2 and PA, and catalyzes both transcription and replication of the RNA genome. PB1 is a catalytic subunit of RNA polymerization and a core of the subunit assembly. The subunit binding sites were mapped at about several hundred amino‐acid size. Fine mapping of the subunit binding sites was determined. The PB1‐PA binding regions were mapped within in the N‐terminal 25 amino acids of PB1 and 668–692 of PA. PB1 and PB2 interacted within wider regions, 600–757 of PB1 and 51–259 of PB2. In these amino‐acid spans, 206–259 of PB2 may be the most important region of PB1 binding and 718–732 of PB1 may be the most important region of PB2 binding because the binding activity was lost when the regions were lost in the subunits. The additional regions contributed to strong binding of these subunits.